(untitled) (Jurnal Simki Economic, 2024)
The existence of a positive Word of Mouth marketing strategy and product quality can increase the tendency of consumers to make purchasing decisions on products. This study aims to examine the effect of Word of Mouth and product quality on purchasing decisions for coffee products at the Gisting Coffee Roastery business in Gisting District, Lampung. This research method uses a quantitative approach with data collection through questionnaires distributed to 67 respondents. Data analysis was carried out using partial hypothesis testing (t-test) and simultaneous hypothesis testing (F-test). The results of this study indicate that Word of Mouth and product quality simultaneously have a significant effect on purchasing decisions for coffee products at the Gisting Coffee Roastery business in Gisting District, Lampung.